(untitled) (Colombia Medica, 2017)
Dear editors, cordial greetings As a group of researchers and professionals signing this letter to the editors, respectfully, we want to make a series of observations and reflections regarding the article “Afro-Colombian ethnicity, a paradoxical protective factor against dengue”1 , published in your prestigious journal. We considered that the article in question lightly concludes that the Afro-Colombian population present a lower risk of complications compared to the non-Afro-Colombian population. This situation, besides of not being completely based on data and facts that it describes and analyzes, is an assertion that can be a source of deeply disorientation for the Colombian health services, upon a time these conclusions get disseminated, and it can also mistakenly indicate to Afro-Colombian people that the risk of complications is lower in the presence of a virus causing a dengue disease.